EMPLOYEE PERFORMANCE IN IMPROVING ACADEMIC SERVICES: A STUDY ON ACADEMIC PERSONNEL AT FACULTY OF ADMINISTRATIVE SCIENCES OF BRAWIJAYA UNIVERSITY - Aminah, Siti; Hayat, Ainul; Hanafi, Imam (Erudio Journal of Educational Innovation, 2025)
Employee performance in improving academic services was accentuated in this study. With respect to the context of higher education, employee performance among educational personnel is considered a key factor to achieving institutional goals. A survey in 2021 on the management of Faculty of Administrative Sciences highlighted time inefficiency amidst the educational personnel playing a role to interfere academic services for students. A number of students sued that any procedures of academic services were supposed to be less time-consuming. Moreover, this study was conducted by means of Indicators of Elements for performance assessment in relevance with Hasibuan’s in Lubis (2018: 4). Findings revealed results of job performance assessments of which criteria were composed of quality and quantity of personnel: the former discussing how good and helpful they were at work, while the latter speaking of workload they could manage and complete. As a matter of a fact, workload for educational personnel was composed of their respective main tasks and multitasking ability to manage other tasks for maximum coverage, but less than 100%. In addition, some inhibiting factors were also unwrapped, which included personality and behavior aspects. It was found that the personnel were not so friendly, lacking of institutional training programs, and consuming too much time for giving good services to students. In a nutshell, to reinforce academic services, it is necessary that the educational personnel be supported with proper training programs to master and run required duties and functions well, adequate technology systems, and SOPs for specific services.